Successful Endoscopic Management of Fish Bone Embedded into the Bladder Wall - Koichi Kodama; Mitsuo Ofude; Isamu Motoi; Yoshinobu Hinoue; Katsuhiko Saito (Case Reports in Medicine)
We report a case of a pyogenous vesical abscess resulting from an ingested fish bone embedded in the bladder wall that was treated endoscopically in an asymptomatic man. Computed tomography of the abdomen showed a linear radiopaque structure in the thickened left anterolateral wall of the bladder. Cystoscopy revealed a protruding mass, covered with normal-appearing mucosa, with outflow of pus from a shallow recess. Histopathological findings indicated that the transurethrally removed linear structure, located in the submucosa, was compatible with fish bone. A high index of suspicion should be maintained for the correct diagnosis to be made.